Evidence for altered insulin signalling in the brains of genetic absence epilepsy rats from Strasbourg. (25th May 2020) - Sekar, Sathiya; Marks, Wendie N.; Gopalakrishnan, Venkat; Greba, Quentin; Snutch, Terrance P.; Howland, John G.; Taghibiglou, Changiz
Abstract: Insulin‐mediated signalling in the brain is critical for neuronal functioning. Insulin resistance is implicated in the development of some neurological diseases, although changes associated with absence epilepsy have not been established yet. Therefore, we examined the major components of PI3K/Akt‐mediated insulin signalling in cortical, thalamic, and hippocampal tissues collected from Genetic Absence Epilepsy Rats from Strasbourg (GAERS) and Non‐Epileptic Control (NEC) rats. Insulin levels were also measured in plasma and cerebrospinal fluid (CSF). For the brain samples, the nuclear fraction (NF) and total homogenate (TH) were isolated and investigated for insulin signalling markers including insulin receptor beta (IRβ), IR substrate‐1 and 2 (IRS1 & 2), phosphatase and tensin homologue (PTEN), phosphoinositide 3‐kinase phospho‐85 alpha (PI3K p85α), phosphatidylinositol 4, 5‐bisphosphate, phosphatidylinositol (3, 4, 5)‐trisphosphate, protein kinase B (PKB/Akt1/2/3), glucose transporter‐1 and 4 (GLUT1 & 4) and glycogen synthase kinase‐3β (GSK3β) using western blotting. A significant increase in PTEN and GSK3β levels and decreased PI3K p85α and pAkt1/2/3 levels were observed in NF of GAERS cortical and hippocampal tissues. IRβ, IRS1, GLUT1, and GLUT4 levels were significantly decreased in hippocampal TH of GAERS compared to NEC. A non‐significant increase in insulin levels was observed in plasma and CSF of GAERS rats. An insulin sensitivity assay showed decreased p‐Akt level in cortical and hippocampal tissues. Together, altered hippocampal insulin signalling was more prominent in NF and TH compared to cortical and thalamic regions in GAERS. Restoring insulin signalling may improve the pathophysiology displayed by GAERS, including the spike‐and‐wave discharges that relate to absence seizures in patients.